The power of youth - Giordano Marmone (Ateliers d'Anthropologie)
Instead of attempting to understand “young people” and “youth” through categories considered universal, it seems more fruitful to examine local productions of age categories. Among the Samburu—pastoralists of northern Kenya, where age is the foundation of individual categorisation and of an egalitarian sociopolitical organisation—youth is “non-existent,” and political authority is among the skills instilled early through training, in the same way as economic tasks. In the very particular context of musical training and the rivalries it provokes for the position of soloist, leadership skills stand out in certain cases. Musical activity, with its ability to bring distinguished personalities to light from before the age of circumcision, occupies a very central place in this power-assertion process at the individual level. As a member of a society sometimes characterised as “gerontocratic,” the Samburu young person actually appears to be the protagonist of a self-generated process of personal political authority creation, much earlier than previously imagined.